Total Flavonoid Levels of Ethanol Extract of Lemongrass Leaves and Thatch Grass Leaves Using UV-VIS Spectrophotometry - Nuryadin, Yudhi; Naid, Tadjuddin; Dahlia, Andi Amaliah; Dali, Seniwati (Window of Health : Jurnal Kesehatan, 2018)
Lemongrass Leaves (Cymbopogoncitratus DC.) and Thatch Grass Leaves (Imperata cylindrical (L.)Raeusch) are medicinal plants belong to similary family. Their activity as natural antioxidant sources because it’s contains the flavonoids compound. This study aimed to determine the total flavonoid content on the ethanol extract of lemongrass leaves and the thatch grass leaves using UV-Vis spectrophotometry. The extraction wasdone by maceration methodusing ethanol. The first sample is 3,95% lemongrass leaves, and the second one is 2,98% thatch grass leaves. The qualitative analysis by TLC method with the eluent ratio n-Hexane:ethyl acetate (6:4) showed that both samples positively contain flavonoids. The quantitative analysis by spectrophotometry at the maximum wavelength 431 nm showed that total flavonoid content in the first sample is 2,8666 % and the second sample is 3,4866 %.